2010
DOI: 10.1111/j.1750-3841.2010.01567.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Combined Microwave–Hot Air Roasting of Malt Based on Energy Consumption and Neo‐Formed Contaminants Content

Abstract: An important goal for research institutions and the brewery industry is to produce colored malt by combining microwave and hot air roasting, while saving energy, getting desirable color, and avoiding the formation of carcinogenic and toxic neo-formed contaminants (NFCs). Therefore, one objective of this study was to compare energy consumption and content of NFCs during roasting of malt by hot air-only and combined microwave-hot air processes as well as to determine the effect of specific power, microwave proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 21 publications
0
16
0
2
Order By: Relevance
“…20,21,174 One interpretation of these associations is that modern foods, replete with appetite-enhancing AGEs, undermine host defenses, while promoting inflammation. A further interpretation is that the ‘healthy’ human baseline has shifted to a phenotype which displays substantial overlap with ‘prediabetes’.…”
Section: Ages and Diabetes Mellitus: A Paradigm Shiftmentioning
confidence: 99%
“…20,21,174 One interpretation of these associations is that modern foods, replete with appetite-enhancing AGEs, undermine host defenses, while promoting inflammation. A further interpretation is that the ‘healthy’ human baseline has shifted to a phenotype which displays substantial overlap with ‘prediabetes’.…”
Section: Ages and Diabetes Mellitus: A Paradigm Shiftmentioning
confidence: 99%
“…Despite being formed at much lower concentrations, HMF and furfural have both been used as Maillard reaction markers (Ameur et al 2008). Several studies have reported that HMF exists in many carbohydrate-rich food products, such as bakery products (Ameur et al 2008;Gokmen et al 2008), malt (Akkarachaneeyakorn et al 2010), fruit juices (Gokmen and Acar 1999;Versari et al 2008), soft drinks (Lo et al 2008), honey (Fallico et al 2004;Spano et al 2009), coffee (Arribas-Lorenzo anddel Campo et al 2010), infant foods (Rada-Mendoza et al 2002;Gokmen and Senyuva 2006), and beer (Saison et al 2009;Wu et al 2009). HMF is known to be cytotoxic, irritating to eyes, upper respiratory tract, skin and mucous membranes at high concentrations (Capuano and Fogliano 2011).…”
Section: Introductionmentioning
confidence: 96%
“…Specialty beers are produced from specialty malt, and the latter is produced by adapting the normal drying process of pilsner malt. Specialty malts can be divided into categories according to their color: colored, coffee, chocolate, caramel, roasted malt, black malt (Woffenden et al 2001;Akkarachaneeyakorn et al 2010). It was stated that components contributing to malt color include colored low molecular weight Maillard reaction products, melanoidins, oxidised polyphenols, and products of sugar caramelisation; sugar caramelisation only being important in very dark malts and roasted barley.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, according to other authors (Giese, 1992;Akkarachaneeyakorn & Birlouez-Aragon, 2010) microwave treatment reduces process energy costs. Energy consumption for microwave drying (about 0.6 kW for the longest tested treatment) was about a half of that of the conventional oven (1.34 kW).…”
Section: Effect Of Microwave Treatments On Hazelnut Roasting and Tastementioning
confidence: 99%
“…This phenomenon is time and energy consuming. In a microwave drying system, the product heating is associated with a volumetric heat generation, which leads to higher internal temperature resulting in an increase in internal vapour pressure which helps to push liquid flow towards the surface, producing higher drying rates (Akkarachaneeyakorn & Birlouez-Aragon, 2010). In a conventional roaster, the temperature increase to 120-160°C in nuts needs about one hour whereas microwave heating requires few minutes.…”
mentioning
confidence: 99%